GENDER EQUALITY AND WOMEN’S EMPOWERMENT AS A MEASNS OF REDUCING POVERTY - Takwi, Asangbeng Collins (Graduate School of International Studies Ajou University, 2013)
ABSTRACT Over the years, the Cameroon government has been making efforts to reduce poverty in rural areas, but attaching very little importance to gender equality and women empowerment. Recently some strides have been made by the government in this direction but the consequence can only be felt in some urban areas, while there is still overt discrimination or inequality between men and women. This result has been the continuous dependence of women on men support, leading to poverty among the women. This thesis hopes to analyze the role of gender equality and women empowerment in reducing poverty in rural areas of Cameroon. It hopes to bring out evidence on the effects of women’s access to markets and decision making within the household on poverty reduction. This will be analyzed using the capability approach of Amartya Sen, in his book Development as Freedom and some of the work of Jeffrey Sachs in his book titled The End of Poverty
학위논문(석사)아주대학교 국제대학원 :NGO학과,2013. 8